Life, death and sacrifice : women and family in the Holocaust - Hertzog, Esther (Gefen, 2008)
Gender and family studies of the Holocaust : the development of a historical discipline / Judith Tydor Baumel -- Motherhood under siege / Dalia Ofer -- "We're all well and hoping to hear the same from you soon--" : the story of a group of families / Irith Dublon-Knebel -- 1943 : the flight from home / Lidia Sciama -- "Camp families" in Ravensbrück and the social organization of Jewish women prisoners in a concentration camp / Judith Buber Agassi -- The persecution and murder of German and German-Jewish women between 1933 and 1945 / Barbara Distel -- Racialised gender, gendered race and gendered-racialised academia : female-Jewish anthropologists in Vienna / Herta Nöbauer -- (Re)-interpreting stories of sexual violence : the multiple testimonies of Lucille Eichengreen / Kirsty Chatwood -- Nazi differentiations mattered : ideological intersections of sexualized violence during national socialist persecution / Helga Amesberger, Brigitte Halbmayr -- Social base of racial othering in Nazi society : the racial community and women's agency in denunciatory practices / Vandana Joshi -- Sophie Scholl : an exploration of a young woman's courage in Nazi Germany / Annette Dumbach -- Jewish political prisoners in Ravensbrück concentration camp / Rochelle G. Saidel -- Gender as a factor in rescuers of Jews during the Holocaust / Eva Fogelman -- Past and present in my mother's Holocaust memories / Esther Hertzog -- Gender, identity and family in the European Holocaust film : the Jewess as virgin and whore / Esther Fuchs